The Potential of Tiger Prawn Fry from Delta Mahakam, East Kalimantan Indonesia - Bob Suroso; Johannes Hutabarat; Norma Afiati (International Journal of Science and Engineering, 2014)
Most of the life cycle of tiger prawns were estuarine (Delta Mahakam). In the juvenile stage life in estuarine and the adult stage in marine. The research objective is to assess the potential of the tiger prawn fry catches in the Mahakam Delta, as a source of tiger prawn fry in the Mahakam Delta area farms. Research using interviews and descriptive analysis through monitoring with fishermen. The results showed that the fry tiger prawn from the Delta Mahakam there on the beaches or the edge of the sea where the water is shallow and slightly brackish, as in the Delta Mahakam. Fry can be captured by using rumpon. Tiger prawns fry from Delta Mahakam durability is relatively higher than fry from the hatchery. However, the number and continuity of fry very limited because it depends on the season. Abundance of fry is determined by the number of larvae produced in the wild and their survival is greatly influenced by the availability of food. Doi: 10.12777/ijse.6.1.43-46 [How to cite this article: Suroso, B., Hutabarat, J., and Afiati, N. (2013). The Potential of Tiger Prawn Fry from Delta Mahakam, East Kalimantan Indonesia, International Journal of Science and Engineering, 6(1),43-46. Doi: 10.12777/ijse.6.1.43-46